HEPATOSPLENIC SCHISTOSOMIASIS-ASSOCIATED CHRONIC PORTAL VEIN THROMBOSIS: RISK FACTOR FOR HEPATOCELLULAR CARCINOMA? - George Felipe Bezerra Darce; Fabio Ferrari Makdissi; Sabrina de Mello Ando; Gilton Marques Fonseca; Jaime Arthur Pirola Kruger; Fabricio Ferreira Coelho; Manoel de Souza Rocha; Paulo Herman (ABCD: Arquivos Brasileiros de Cirurgia Digestiva, 2023)
ABSTRACT BACKGROUND: Hepatosplenic schistosomiasis is an endemic disease prevalent in tropical countries and is associated with a high incidence of portal vein thrombosis. Inflammatory changes caused by both parasitic infection and portal thrombosis can lead to the development of chronic liver disease with potential carcinogenesis. AIMS: To assess the incidence of portal vein thrombosis and hepatocellular carcinoma in patients with schistosomiasis during long-term follow-up. METHODS: A retrospective study was conducted involving patients with schistosomiasis followed up at our institution between 1990 and 2021. RESULTS: A total of 126 patients with schistosomiasis were evaluated in the study. The mean follow-up time was 16 years (range 5–31). Of the total, 73 (57.9%) patients presented portal vein thrombosis during follow-up. Six (8.1%) of them were diagnosed with hepatocellular carcinoma, all with portal vein thrombosis diagnosed more than ten years before. CONCLUSIONS: The incidence of hepatocellular carcinoma in patients with schistosomiasis and chronic portal vein thrombosis highlights the importance of a systematic long-term follow-up in this group of patients.